Engineering Economic Systems: Past, Present and Future - Brandeau, Margaret (2024)
At Stanford, engineering economic systems emerged as a discipline in the late 1960’s. The department’s curriculum had four central areas: decision analysis, optimization, economic sciences, and dynamic systems. The emphasis was on both practice and theory. The Management Science and Engineering Department at Stanford (MS&E), founded in 2000, is an outgrowth of the former Engineering Economic Systems Department. MS&E focuses on the codesign of engineering platforms and social systems in the 21st century, at scale and with pervasive data. The goal is to understand, design, implement, and control large-scale, integrated systems of people and machines. The intellectual spectrum ranges from analytics and computation to social and behavioral sciences. This article describes examples of past and present projects in the areas of energy, education, the economy, the environment, and health. Looking to the future, we are likely to see the continual emergence of new technologies, increasing amounts of data, increasing levels of connectivity, advances in computing, ubiquity of machine learning and artificial intelligence, and increasing importance of the need to address social and environmental problems. These will lead to new ways of analyzing problems and rich new opportunities for the tools of engineering economic systems to have impact.